2001
DOI: 10.1161/hh1201.092994
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C ε–Src Modules Direct Signal Transduction in Nitric Oxide–Induced Cardioprotection

Abstract: Abstract-An essential role for protein kinase C ⑀ (PKC⑀) has been shown in multiple forms of cardioprotection; however, there is a distinct paucity of information concerning the signaling architecture that is responsible for the manifestation of a protective phenotype. We and others have recently shown that signal transduction may proceed via the formation of signaling complexes (Circ Res. 2001;88:59 -62

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
81
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 47 publications
6
81
0
Order By: Relevance
“…There is an extensive body of work implicating ROS dependent mechanisms in the triggering of delayed preconditioning by ischemia, exercise or other preconditioning stimuli (33)(34)(35)(36)(37). Following the trigger the next step in late preconditioning requires signaling through pathways that involve key protective kinases including PKC epsilon and PKC epsilon/Src containing modules (38,33). The ability of sulindac to induce preconditioning markers dependent on both PKC activity and ROS is strong evidence that sulindac is functioning as a chemical preconditioning agent.…”
Section: Discussionmentioning
confidence: 99%
“…There is an extensive body of work implicating ROS dependent mechanisms in the triggering of delayed preconditioning by ischemia, exercise or other preconditioning stimuli (33)(34)(35)(36)(37). Following the trigger the next step in late preconditioning requires signaling through pathways that involve key protective kinases including PKC epsilon and PKC epsilon/Src containing modules (38,33). The ability of sulindac to induce preconditioning markers dependent on both PKC activity and ROS is strong evidence that sulindac is functioning as a chemical preconditioning agent.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PKC can directly bind to and activate Src (Moyers et al, 1993;Vondriska et al, 2001). Pyk2 activation was also found to be dependent on PKC activity.…”
Section: Discussionmentioning
confidence: 99%
“…Using whole cardiac cell Iysates (52, 142), our previous studies identified many molecular participants that comprise the cardiac PKCE signaling subproteome, however, information regarding the subcellular localization of PKCE associated proteins, which is essential to the mapping of this subproteome, is unknown. The formation and activation of specific PKCE signaling complexes at different subcellular compartments has been implicated to have significant functional consequences (12,172,173). Characterization of the subcellular distribution of PKCE complexes should provide key insights into the signaling mechanisms underlying the cardiac phenotypes observed in response to PKCE activation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, specific modules are formed within subproteomes in response to different stimuli (145,160,172). Instead of attempting to Simultaneously examine all proteins in cardiac cells, we focus our research on characterization myocardial subproteomes that are critically involved in the development of ischemic injury and cardioprotection, especially the subproteomes of protein kinases associated with cardioprotection (136,142,172).…”
mentioning
confidence: 99%
See 1 more Smart Citation